QLTI-09. DEFINING GLOBAL BENCHMARK OUTCOMES FOR TRANSSPHENOIDAL SURGERY OF PITUITARY ADENOMAS: A MULTICENTER ANALYSIS OF 2862 CASES. (14th November 2022) - Drexler, Richard; Rotermund, Roman; Smith, Timothy; Kilgallon, John; Honegger, Jürgen; Nasi-Kordhishti, Isabella; Gardner, Paul; Gersey, Zachary; Abdallah, Hussein; Jane, John; Marino, Alexandria; Knappe, Ulrich; et al.
Abstract: Benchmarks are important to measure and aid in improve outcomes for surgical procedures. However, best achievable results that have been validated internationally for transsphenoidal surgery are not available. Therefore, we aimed to establish robust, standardized outcome benchmarks for transsphenoidal surgery of pituitary adenomas. A total of 2862 transsphenoidal tumor resections from 12 high-volume centers in 4 continents were analyzed. Patients were risk stratified and the median values of each center's outcomes were established. The outcome benchmark was defined as the 75 th percentile of all median values for a particular outcome as defined by Staiger et al. Out of 2862 patients, 1201 (41.9%) defined the benchmark cohort. The proportion of benchmark cases contributing to the final cohort ranged across centers between 22.1% to 59.7%. Within the benchmark cases, 928 (73.3%) patients underwent microscopic (MTS) and 263 (21.9%) patients endoscopic endonasal resection (EES). The overall postoperative complication rate was 18.9% with an in-hospital mortality between 0.0-0.8%. Benchmark cutoffs were ≤ 3.3% for reoperation rate, ≤ 4.6% for cerebrospinal fluid leak requiring intervention, and ≤ 15.3% for transient diabetes insipidus. At 6 months follow-up, benchmark cutoffs were calculated as follows: readmission rate: ≤ 7.1%, new hypopituitarism ≤ 15.5%, new neurological deficit ≤ 1.2%, tumor remnant ≤ 25.5%. This analysis defines benchmark values for transsphenoidal resection of pituitary adenomas targeting morbidity, mortality, surgical and tumor-related outcomes. The benchmark cutoffs can be used to assess different centers, patients' populations, and novel surgical techniques.